2018
DOI: 10.1111/jocn.14659
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a structured nursing intervention program on maternal stress and ability among mothers of premature infants in a neonatal intensive care unit

Abstract: The results of the study could help neonatal nurses to develop an appropriate nursing intervention for parents with premature infants in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 21 publications
1
20
0
8
Order By: Relevance
“…A researcher in Rwanda, [24] studied the parental perception of stress in the NICU and found that what constituted a stressful event, was the appearance and behaviour of the baby. When an infant is born in Rwanda, the whole community is excited to support the family and offer the mother help in caring for the baby in her home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A researcher in Rwanda, [24] studied the parental perception of stress in the NICU and found that what constituted a stressful event, was the appearance and behaviour of the baby. When an infant is born in Rwanda, the whole community is excited to support the family and offer the mother help in caring for the baby in her home.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified the challenges for parents with a preterm infant in the NICU, [23,24] and others included educational interventions by nurses to increase parental knowledge and decrease stress. [7,18,[25][26][27] There have been no studies conducted in Rwanda evaluating the effectiveness of a parental education intervention in the NICU.…”
Section: Introductionmentioning
confidence: 99%
“…For the neonatal population, the main stressors reported by the families were the alteration of parenting, 2,3,9,11,37,39-43 the appearance and behavior of the child, 2,3,9,11,14,37,38,[42][43][44]46 the care environment, 11,25,38,42,44,46 and communication with health care staff. 40,44,46 These stressors are linked to the most frequently used measure of parental stress, the Parental Stress Scale (PSS): NICU.…”
Section: Neonatal Carementioning
confidence: 99%
“…Other interventions involved fostering communication with parents, 2,3,37,39,40,46 taking into account the stress factors present. 3,11,24,31,42,44 For instance, Akkoyun and Arslan 37 suggested providing support to mothers by giving them information. Finally, other recommended interventions involved encouraging parents to use social support during this experience to enable them to become actively involved as parents.…”
Section: Neonatal Carementioning
confidence: 99%
“…Hospitalization of the neonate for a longer period results in family members; mothers in particular, feel they are isolated from their babies and their emotions turns into stress. Intervention to the mothers in the form of educational information and psychological support were proved to be effective in reducing the maternal psychological problems in the NICU [7]. Performing proper orientation for the parents of the preemies, especially mothers, will help them familiarize with the NICU environment.…”
Section: Res Pediatr Neonatolmentioning
confidence: 99%